2002
DOI: 10.1038/sj.bjp.0704654
|View full text |Cite
|
Sign up to set email alerts
|

Mouse β3a‐ and β3b‐adrenoceptors expressed in Chinese hamster ovary cells display identical pharmacology but utilize distinct signalling pathways

Abstract: 1 This study characterizes the mouse b 3a -adrenoceptor (AR) and the splice variant of the b 3 -AR (b 3b -AR) expressed in Chinese hamster ovary cells (CHO-K1). 2 Stable clones with high (*1200), medium (*500) or low receptor expression (*100 fmol mg protein 71 ) were determined by saturation binding with [ 125 I]-(7)-cyanopindolol. Competition binding studies showed no signi®cant di erences in a nity of b-AR ligands for either receptor. 3 Several functional responses of each receptor were measured, namely ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 36 publications
3
91
2
Order By: Relevance
“…Second, ␤ 3 -AR in the IAS smooth muscle may have a large number of spare receptors. Third, ␤ 3 -AR may represent a heterogeneous population such as ␤ 3a -and ␤ 3b -ARs, as suggested by the recent studies in CHO (Hutchinson et al, 2002). Furthermore, the activation and signal transduction of such a ␤ 3a -and ␤ 3b -AR complex may prevent the full potency of the ␤ 3 -AR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Second, ␤ 3 -AR in the IAS smooth muscle may have a large number of spare receptors. Third, ␤ 3 -AR may represent a heterogeneous population such as ␤ 3a -and ␤ 3b -ARs, as suggested by the recent studies in CHO (Hutchinson et al, 2002). Furthermore, the activation and signal transduction of such a ␤ 3a -and ␤ 3b -AR complex may prevent the full potency of the ␤ 3 -AR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Studies including only β 3 -adrenoceptors reported BRL 37,344 to be a full agonist for cAMP accumulation in intact CHO cells at human and mouse but a partial agonist at rat β 3 -adrenoceptors (Blin et al 1994;Liggett 1992). BRL 37,344 has similar affinity for both splice variants of the murine β 3 -adrenoceptor, but its effects, similar to that of many other agonists, are somewhat lower at the β 3b -compared with the β 3a -adrenoceptor, as the former couples to both G s and G i proteins (Hutchinson et al 2002). Given that the selectivity of BRL 37,344 for β 3 -relative to other β-adrenoceptor subtypes is only moderate in binding studies, the question as to whether it has intrinsic efficacy at β 1 -and/or β 2 -adrenoceptors becomes of major importance to determine its usefulness in functional studies.…”
Section: Adrenaline and Noradrenalinementioning
confidence: 95%
“…Moreover, the organization of the β 3 -adrenoceptor gene differs between species, with, e.g., the human gene having only two exons (the second one comprising only the final six amino acids), whereas the rodent gene has three exons (although the third does not code for any amino acid residues) . Finally, the murine receptor has splice variants, which are differentially expressed in tissues (Evans et al 1999) and couple to Naunyn-Schmiedeberg's Arch Pharmacol (2007) 374:385-398distinct signaling pathways (Hutchinson et al 2002;.…”
mentioning
confidence: 99%
“…In the case of the mouse ␤ 3 -adrenoceptor, alternative splicing results in the expression of two splice variants, the ␤ 3a -and ␤ 3b -adrenoceptor (Evans et al, 1999). Functional studies of the ␤ 3a -and ␤ 3b -adrenoceptor expressed in Chinese hamster ovary (CHO-K1) cells, using either extracellular acidification rate (ECAR) in the cytosensor microphysiometer or cAMP generation as bioassays, have shown that the ␤ 3a -and ␤ 3b -adrenoceptor couple to Gs, whereas the ␤ 3b -adrenoceptor also couples to Gi (Hutchinson et al, 2002). Both splice variants also couple to extracellular signal-related kinases 1 and 2 (ERK1/2) by a mechanism that does not involve either the generation of cAMP or activation of Gi, suggesting that additional pathways can be activated that are not linked sequentially to the classic pathways (Hutchinson et al, 2002).…”
mentioning
confidence: 99%
“…Functional studies of the ␤ 3a -and ␤ 3b -adrenoceptor expressed in Chinese hamster ovary (CHO-K1) cells, using either extracellular acidification rate (ECAR) in the cytosensor microphysiometer or cAMP generation as bioassays, have shown that the ␤ 3a -and ␤ 3b -adrenoceptor couple to Gs, whereas the ␤ 3b -adrenoceptor also couples to Gi (Hutchinson et al, 2002). Both splice variants also couple to extracellular signal-related kinases 1 and 2 (ERK1/2) by a mechanism that does not involve either the generation of cAMP or activation of Gi, suggesting that additional pathways can be activated that are not linked sequentially to the classic pathways (Hutchinson et al, 2002). Therefore, it is possible that the study of a variety of ␤ 3 -adrenoceptor ligands may reveal differences in intrinsic activity (IA) at the different signaling pathways and thus shed light on the mechanisms involved.…”
mentioning
confidence: 99%